The status quo of digital transformation in insurance sales: an empirical analysis of the german insurance industry Status quo der digitalen Transformation im Versicherungsvertrieb: Eine empirische Analyse der deutschen Versicherungswirtschaft - Eckert, Christian; Eckert, Johanna; Zitzmann, Armin (Zeitschrift für die gesamte Versicherungswissenschaft, 2021)
In this paper, we focus on the impact of digital transformation on traditional ways to sell insurance products. Our goal is to investigate how widespread the use of digital technologies in insurance sales is and which values of these digital technologies are perceived by insurance intermediaries. Moreover, we aim to analyze underlying influencing factors in this regard. We conducted a survey in July 2020, i.e., after the first wave of COVID-19, in which 671 exclusive agents from various insurance companies, independent agents and independent brokers from Germany participated. Our results show that even at this point of time, in a high proportion of sales workforces, digital transformation is not yet very advanced. Further analyses show that exclusive agents and younger people are further ahead in digital transformation even though COVID-19 pushes digital life across all ages and social classes. Based on our results, we derive initial recommendations for action for the insurer.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Digital transformation; Empirical study; German insurance industry; Insurance sales; Survey